2021
DOI: 10.1016/j.ijid.2020.12.079
|View full text |Cite|
|
Sign up to set email alerts
|

Utility of the antigen test for coronavirus disease 2019: Factors influencing the prediction of the possibility of disease transmission

Abstract: Rapid antigen testing (RAT) for coronavirus disease 2019 (COVID-19) has lower sensitivity but high accuracy during the early stage when compared to reverse transcription quantitative polymerase chain reaction (RT-qPCR). The aim of this study was to investigate the concordance between RAT and RT-qPCR results, and their prediction of disease transmission. Methods: This single-center retrospective observational study of inpatients with COVID-19 was conducted from March 6 to June 14, 2020. Nasopharyngeal swabs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
9
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
1
9
1
1
Order By: Relevance
“…Kohmer et al reported that the antigen-detecting rapid diagnostic test correlated better with cell culture infectivity in vitro than RT-qPCR (61.8%-82.4% vs 51.6%) [7]. Our previous study also implied the utility of qualitative antigen testing in predicting the appropriate duration of quarantine [16]. Qualitative antigen tests generally tend to be less sensitive, and false-negative results in contagious patients have been a challenge.…”
mentioning
confidence: 53%
“…Kohmer et al reported that the antigen-detecting rapid diagnostic test correlated better with cell culture infectivity in vitro than RT-qPCR (61.8%-82.4% vs 51.6%) [7]. Our previous study also implied the utility of qualitative antigen testing in predicting the appropriate duration of quarantine [16]. Qualitative antigen tests generally tend to be less sensitive, and false-negative results in contagious patients have been a challenge.…”
mentioning
confidence: 53%
“…Of these, seven of eight RAT-positive samples (88%) and three of ten RAT-negative samples (30%) were positive on viral culture [7]. There were fewer samples that were positive based on viral culture in our study than in the study by Yamamoto et al [1] because a higher proportion of the samples in our study were collected >9 days after symptom onset. Positive viral culture results are known to be associated with the number of days since the disease onset [8].…”
contrasting
confidence: 54%
“…RAT might be a useful indicator of infectiousness, which can be helpful to control infection. However, further studies with larger sample size are warranted to confirm this observation.Immunochromatographic rapid antigen tests (RATs) for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are simple to perform and have a relatively low cost but they have a low sensitivity [1][2][3]. A potential advantage of the low sensitivity of RATs is that they do not remain positive during the long period of low viral excretion after infectiousness has passed [4].…”
mentioning
confidence: 99%
See 2 more Smart Citations